A Fluorescence Resonance Energy Transfer Probe Based on DNA-Modified Upconversion and Gold Nanoparticles for Detection of Lead Ions - Wang, Yue; Lv, Menghua; Chen, Zehan; Deng, Zilong; Liu, Ningtao; Fan, Jianwei; Zhang, Weixian (Frontiers in Chemistry, 2020)
We reported a new sensor for specific detection of lead ions (Pb2+) in contaminated water, based on fluorescence resonance energy transfer (FRET) between upconversion nanoparticles (UCNPs) as donors and gold nanoparticles (Au NPs) as receptors. The UCNPs modified with Pb2+ aptamers could bound to Au NPs, which were functionalized with complementary DNA through hybridization. The green fluorescence of UCNPs was quenched to maximum rate of 80% due to the close proximity between energy donor and acceptor. In the presence of Pb2+, the FRET process was broken because Pb2+ induced the formation of G-quadruplexes from aptamers, resulting in unwound DNA duplexes and separated acceptors from donors. The fluorescence of UCNPs restored and relative intensity had a significant linear correlation with Pb2+ concentration from 0 to 50 nM. The sensor had a detection limit as low as 4.1 nM in a buffer solution. More importantly, the sensor exhibited specific detection of Pb2+ in complex metal ions, demonstrating a high selectivity in practical application. The developed FRET prober may open up a new insight into specific detection of environmental pollution.